A STUDY OF IMPACT OF DETERMINANTS OF PATIENTS AND HEALTH SYSTEM DELAY ON TUBERCULOSIS DIAGNOSIS AND TREATMENT IN BANGALORE - Devaru, Jagadish Siddalinga; Sakranaik, Saraswathi; V, Divakar S (Indian Journal of Community Health, 2012)
Setting: TU/DMCs of Bangalore city. India. All new sputum positive patients registered to the selected TU/DMCs were interviewed. A total of 468 patients aged above 20 years were enrolled. The study period was from January to June 2009. Objectives: To track the delay in diagnosis and treatment of patients reporting to tuberculosis units and microscopy centers. Design: A cross sectional study. TU/DMCs were randomly selected. A pretested questionnaire was administered to collect data. Results: The study population had 326 (69.7%) males. The mean age of study population was 38.5 years. 74.4% were married, 20.7% were illiterates, 27.8% were daily wagers, 10.5% were unemployed. The median and mean total delays from development of cough to diagnosis were 41 days and 36.04 days; the median and mean patient delay was 24 days and 20.7 days, and health system delay was 18 and 15.31 days respectively. There was a significant difference among the different age group of patients with older people having longer patient delay (p<0.0001). Lower income, illiteracy, unemployment, showed significant association with patients delay (p<0.0001). Alcohol intake and smoking habit among the male patients had significant association for longer patient delay (p=0.00004). Health seeking behavior like self medication, also had longer patient delay. Other socio demographic factors had no significant influence on the patient delay. Longer health system delay was found among patients who visited general practitioners and Ayurvedic medicine. Conclusion: More specific and effective health education of the general public on tuberculosis and seeking of appropriate medical consultation are likely to improve case detection.